A hierarchically-assembled Fe–MoS2/Ni3S2/nickel foam electrocatalyst for efficient water splitting. Issue 32 (23rd July 2019) - Xue, Jiang-Yan; Li, Fei-Long; Zhao, Zhong-Yin; Li, Cong; Ni, Chun-Yan; Gu, Hong-Wei; Braunstein, Pierre; Huang, Xiao-Qing; Lang, Jian-Ping
Abstract : Hierarchically-assembled Fe–MoS2 /Ni3 S2 /NF demonstrates excellent HER, OER and full water splitting catalytic performances in an alkaline electrolyte. Abstract : The development of bifunctional non-noble metal electrocatalysts demonstrating high activity and stability for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is of great significance for renewable and clean energy. In this work, we report hierarchically structured integrated Fe–MoS2 /Ni3 S2 /NF (NF = nickel foam) materials prepared by a facile in situ solvothermal method, and among them, the Fe-doped MoS2 was assembled into spine-like nanorods. The optimized electrocatalyst (denoted as Fe–MoS2 /Ni3 S2 /NF-2) demonstrated excellent activity and durability for performing the HER and OER in an alkaline electrolyte (pH = 14) with low overpotentials of 130.6 mV and 256 mV ( vs. RHE) at a current density of 10 mA cm −2, as well as no significant loss in catalytic performance even after 2000 cyclic voltammetry (CV) cycles. An outstanding durability of 180 h could be achieved for OER. The overall water splitting made up of the two-electrode system with Fe–MoS2 /Ni3 S2 /NF-2 as both the anode and the cathode required a voltage of only 1.61 V to drive a current density of 10 mA cm −2 along with an outstanding long-term stability of 20 h, displaying its great potential for application in water splitting. The effective construction of multi-component synergistic structures shows a good pathway for high-performance electrocatalysis and energy storage.